FRI0497 TRABECULAR BONE SCORE AND MALNUTRITION IN A COHORT OF SYSTEMIC SCLEROSIS PATIENTS. (June 2019) - Paolino, Sabrina; Patanè, Massimo; Tomatis, Veronica; Casabella, Andrea; Pizzorni, Carmen; Schenone, Carlotta; Carmisciano, Luca; Signori, Alessio; Cutolo, Maurizio
Abstract : Background: Systemic sclerosis (SSc) is a connective tissue disease characterized by initial microvascular damage, immune system activation and progressive fibrosis of the skin and internal organs.Gastrointestinal (GI) involvement induce malnutrition due to gastroesophageal symptoms, GI dismotility and malabsorption that are related to fibrosis of bowel wall and bacterial overgrowth(1).Therefore the disease is associated with secondary osteoporosis with a few studies evaluating the bone microarchitecture(2). Objectives: To evaluate a relationship between malnutrition and bone microarchitecture detected by trabecular bone score (TBS) in SSc patients. Methods: 38 patients(6 male and 32 female) fulfilling ACR 2013 criteria for SSc underwent DXA to detect quantitative lumbar spine bone mineral density and TBS. DXA also assess body composition with a software that provides the physician quantitative parameters, including free fat mass index (FFMI), that identifies the patient with malnutrition(values <15 kg/m2 in women and 17 kg/m2 in men), according to the ESPEN criteria(3).Body mass index was calculated for all SSc patients and every patient completed a diary reporting GI symptoms possibly related to intestinal disbiosis.Fasting blood samples were obtained in order to analyse some biochemical parameters of malnutrition (total proteins(g/L), albumin(g/L), serum total cholesterol(mg/dl) and blood lymphocyte count (N/mm3).Continue variables were summarized as mean and standard deviation(SD) or median and inter quartile rang (IQR), discrete variables were summarized with count and percentage. Correlation was tested with Pearson or Spearman method. T-test was used to compare TBS between dichotomic groups Uni and multivariate linear regression models were used as well the Multiple R-squared variation was applied. The multivariate linear regression was performed with a stepwise approach to select the best model using highest AIC criteria. Results: The mean age of patients was 64.2±11.3 years with mean disease duration 19.2±7.6 years. 36.8% of patients was found malnourished. The univariate analysis showed that only higher age of patients correlated to lower TBS(p<0.001). The R-squared of multivariate linear regression showed that about 45% of the TBS variations(TBSv) can be explained by the variation of the following variables(age, disease duration, lymphocyte count).Age explains about 25% of the TBSv.Older patients had lower TBS, with approximately 0.05 points of TBS loss every decade(p = 0.001).The presence of symptom possibly related to intestinal disbiosis, added to the model, might explains about 12% more of TBSv. Patients with symptom related to bacterial overgrowth had lower TBS respect to patients without(-0.08), regardless of other variables(p=0.002).Disease duration, added to the model, further explains about 4% more of TBSv and suggest a trend between highest disease duration (regardless of other variables) and higher TBS(p = 0.103).Lymphocyte count added to the model also seems to explain about 4% more of TBSv, in fact lowest number(regardless of other variables) appear to have interference on TBS(p = 0.020) Conclusion: This study shows that a more severe microarchitectural bone defect correlates with gastrointestinal involvement in term of symptom related to intestinal disbiosis and with selected blood biochemical markers of malnutrition. References: [1] Caimmi C et al. 2017 Clin Rheumatol 37(4):987–997. [2] Ruaro B et al. 2018 Rheumatology (Oxford) 1;57(9):1548–1554. [3] Cederholm T et al. 2015 Clin Nutr 34(3):335–340. Disclosure of Interests: None declared